Carlo Crivelli: a strategy for the Marche rebirth - Benedetta Castagna (Janeway JS, 2021)
Carlo Crivelli’s work is dispersed around the world, but significant examples remain in the Italian region of the Marche. This article analyses the benefit of a collaborative approach between Crivelli’s exhibitions in the Marche to propose strategies that would follow a place-based approach and increase the attractiveness of cities and villages where Crivelli’s artworks are displayed. The paper analyses two case studies presenting different approaches to the Crivelli’s art works: the Museum of St Francis displaying the Triptych of Montefiore dell’Aso, and the Church of St. Martin Bishop exhibiting the Polyptych of Monte San Martino in the original location.